The Effect of Tangram Media Assited Think Pair Share Model on Calculation Ability Area and Circumference Plane Geometry - Andromeda, Bravura; Mardiana, Tria; Wijayanto, Sukma (Prosiding University Research Colloquium, 2021)
This research aims to determine the effect of the Think Pair Share model assisted by tangram media on the ability to calculate the area and perimeter of flat shapes in fourth grade students of primary school in Purworejo. This research is a type of pre-experimental research with one group pretest-posttest design. Sampling was selected by saturated sampling. The samples taken were 19 students. The method of data collection is done by using a description test. The validity test uses the product moment formula, while the reliability test uses the Cronbach alpha formula which produces a reliability index of 0.945. Data analysis used parametric statistical techniques, namely the Paired Sample T-Test with the help of the SPSS for Windows version 26.00 program. The results of the analysis of the Data Test of Two Dependent Samples carried out using the Paired Sample T-Test with a t count > t table, which is 17.006 > 2.093 with an Asymp value. Sig. (2-tailed) 0.000 < 0.05. Based on the results of the analysis and discussion, there are difference in the average score of the ability to calculate the area and perimeter of plane geometry, namely the pretest average of 48.1, while the posttest average is 76.8. This shows that there is an influence of the TPS model assisted by Tangram media on the ability to calculate the area and perimeter of plane geometry in fourth grade students of primary school Academic Year 2020/2021.